(untitled) (Dhaka University Journal of Pharmaceutical Sciences, 2021)
Ceftibuten dihydrate is a semisynthetic, orally administered, third generation cephalosporin antibiotic which is effective against most of the pathogens causing infections in the respiratory tract. Complexation of ceftibuten dehydrate (Ligand, L) was performed with hydrated Ni(II) salt (Metal, M) in the ratio of 2:1 (L:M) in aqueous medium at 90 oC. The metal complex was then characterized by spectral techniques and thermal analyses. The FT-IR spectral data of metal complex suggested the monodentate bonding of metal ion to carboxylate group. Spectral evidence also supported the formation of five-membered ring via coordination of metal ion to β-lactam nitrogen and carboxylate group of parent drug. Thermal behavior of ligand and complex were studied. Thus, thermoanalytical (DSC and TGA) results also supported the formation of new metal complex, indicating the successful interaction of metal ion to ligand. Dhaka Univ. J. Pharm. Sci. 20(2): 219-225, 2021 (December)